Comportamento reprodutivo de garanhões da raça Baixadeiro - Lima, Sônia de Sousa Silva (2013)
The horse of Baixadeiro breed is was introduced and adapted in a swamp area in northeastern Brazil, characterized with Baixada Maranhense. This breed was included in the genetic resources conservation program of the National Center for Genetic Resources (EMBRAPA CENARGEN) in year 2002, but remains absent scientific data about its reproductive behavior. Eight stallions with their harems were observed for 12 hours in their natural habitat. The behaviors were identified and distributed in harem maintenance behaviors, identification of sexual receptivity, pre-mating, courtship and mating. After the behavioral assessment were done testicular measurements. Statistical analysis was performed with PROC GENMOD and PROC CORR of SAS. The testis measurements revealed six stallions with normal testes, and two with partial unilateral testicular hypoplasia, which showed higher frequencies for identification of sexual receptivity, courtship, pre-mating and mating than normal testes stallions. Behaviors of identification of sexual receptivity were the most frequent reproductive events in both hypoplasic and normal stallions. The normal younger stallions were most efficient to identify receptive mares (r2 = -0.439) and performed mating (r2 = -870, P = 0.024). Alternatively, the older males showed higher frequency of courted (r2 = 0.652), protection females of their harems (r2 = 0.493) and events of premating (r2 = 0.242). The size of harems ranged 9-20 adult mares and was positively correlated with body condition score (r2 = 0.349) and negatively with age (r2 = - 0.752, P = 0.085). It was concluded that the Baixadeiro stallion in their natural habitat, shows social interactions and sexual activity in a similar pattern to already established for other equine breeds, with special attention to overexpression of sexual activity in animals with gonadal hypoplasia.